Analysis of Porous Silicon Formation on N-type Si (100) using Laser-Assisted Electrochemical Anodization Method - Risa Suryana; Nabila Qurrota Aini (Diponegoro University Semarang Indonesia, 2022)
Porous silicon (PSi) was formed on n-type Si (100) substrates using the laser-assisted electrochemical anodization method. The silicon surface was anodized in the solution of HF (40%) and ethanol (99%) in a ratio of 3:1 at a current density of 20 mA/cm2 for 15 min. The laser was illuminated on a silicon surface during the etching process. PSi surface morphology was characterized by SEM and identification of chemical bonds using FTIR. The highest number of pores, the best pore size homogeneity, and the smallest pore diameter in PSi were formed in Si which was illuminated by a green laser (2.33 eV). In contrast to red (1.91 eV) and purple (3.06 eV) formed irregular pores because of their small number and inhomogeneous size. On the PSi surface, Si-H and Si-O-Si bonds are formed. The number of Si-Hn and Si-O-Si bonds is directly proportional to the number of pores formed in PSi.